2018
DOI: 10.1186/s40104-018-0290-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of galacto-oligosaccharides on growth and gut function of newborn suckling piglets

Abstract: BackgroundMost research on galacto-oligosaccharides (GOS) has mainly focused on their prebiotic effects on the hindgut, but their beneficial effects on the small intestine (SI) have received little attention. Since jejunum is the important place to digest and absorb nutrients efficiently, optimal maturation of the jejunum is necessary for maintaining the high growth rate in the neonate. Therefore, this study investigates the effect of the early intervention with GOS on the intestinal development of the jejunum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“… 21 GOS and FOS are prebiotics which can be fermented by gut microbiota to produce SCFAs, playing advantageous roles for intestinal development and growth. 22 , 23 In addition, MFGM is a protein–lipid complex surrounding the milk fat globules, reported to accelerate the growth of infants and piglets. 24 In the present study, GMF administration during the first week, with the homogeneous average daily feed intake (ADFI) of the creep feed (73.47 vs 69.27 g; SEM = 11.15, P = 0.732), improved the growth performance of piglets during the whole neonatal period, indicating the positive and durable effects of combined GOS, MFGM, and FOS on growth promotion.…”
Section: Discussionmentioning
confidence: 99%
“… 21 GOS and FOS are prebiotics which can be fermented by gut microbiota to produce SCFAs, playing advantageous roles for intestinal development and growth. 22 , 23 In addition, MFGM is a protein–lipid complex surrounding the milk fat globules, reported to accelerate the growth of infants and piglets. 24 In the present study, GMF administration during the first week, with the homogeneous average daily feed intake (ADFI) of the creep feed (73.47 vs 69.27 g; SEM = 11.15, P = 0.732), improved the growth performance of piglets during the whole neonatal period, indicating the positive and durable effects of combined GOS, MFGM, and FOS on growth promotion.…”
Section: Discussionmentioning
confidence: 99%
“…c P < 0.05 means different, P < 0.01 means significantly different, 0.05 < P < 0.10 means tending to be different. Mountzouris et al (2006) reported that increased digestibility of carbohydrate components, such as nitrogen free extract and NDF, of pigs consuming the trans-galactooligosaccharides diet might be due to the improving effect of GOS on the morphology and function of gut (Leforestier et al 2009;Akbari et al 2015;Bhatia et al 2015;Tian et al 2018). Second, other research also found that dietary GOS enhanced net absorption of mineral elements and improved their retention time (Weaver et al 2011;Takasugi et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…MDA level tended to quadratically decrease (P = 0.09) on d 14 and significantly quadratically decreased (P = 0.02) on d 28 with the increased amount of GOS inclusion. Tian et al (2018) showed that piglets fed the diet supplemented with GOS had greater ADG than those fed the basal diet in the third week. In the present study, ADG of the weaned piglets increased during d 0-14 and d 0-28 of the experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of glucagon-like peptide-1 (GLP-1), glucagon-like peptide-2 (GLP-2), insulin-like growth factor 1 (IGF-1), and epidermal growth factor (EGF) levels in intestinal mucosa was conducted using the ProcartaPlex™ multiplex immunoassay kit (Luminex, Austin, TX, USA) as previously reported [31].…”
Section: Methodsmentioning
confidence: 99%